Journey to mother baby care: Implementation of a combined care/couplet model in a Level 2 neonatal intensive care unit. Issue 15 (27th May 2019) - de Salaberry, Julie; Hait, Valoria; Thornton, Kimberly; Bolton, Megan; Abrams, Maria; Shivananda, Sandesh; Kiarash, Maryam; Osiovich, Horacio
Abstract: "Why can't I have my postpartum care in the same room as my baby?" questioned Hilary, a neonatal intensive care unit (NICU) "alumni" parent, during a design event for the new British Columbia's Women's Hospital 70 single family room NICU. This simple yet provocative question was nearly dismissed and the idea of a combined care model lost, since most members of the team thought it was simply "not possible." Hilary did not give up and continued to raise this idea throughout every design event. It was Hilary's fortitude and sharing of her NICU experience that was the inspiration for the MotherBaby Care unit. The voice of one woman has improved the birth experiences of potentially thousands of mothers and their at‐risk newborns. By honoring women's voices and values in health care, positive changes that matter to women, infants, and families can be made. Mothers also shared: "I knew what was best for me was to be with my baby, " "If I could stand up after my C‐section, I would drag my IV pole to be with my baby!", "Teach me how to take care of my premature baby before I am ready to go home!" MotherBaby Care is a combined care or "couplet" care where one NICU nurse provides care for a postpartum mother and her at‐risk newborn in the Level 2 NICU. This review describes the journey from innovation and design to the implementation of the MotherBaby Care model.